Pesantren: a Potrait of Education and Islamic Social History - Akhmad Afnan Fajarudin (Journal of Islamic Education Research, 2024)
Many studies on pesantren have been carried out by academics, both from within and outside the country with various approaches. However, the results are often inconsistent, making them unsatisfactory. This paper aims to explain the existence of pesantren that have existed for six centuries, as well as being the only educational institution owned by indigenous people, and being a driving force in the development of Malay Nusantara civilization. Pesantren also plays a big role in maintaining its traditions in the archipelago. With increasing variety and recognition, it can be concluded that pesantren have a plural, diverse, and non-uniform character.